Engineered Multifunctional Fluorinated Film Based on Semicontinuous Emulsion Polymerization Using Polymerizable Quaternary Ammonium Emulsifiers - Hongzhu Liu; Lingnan Wang; Minhuan Wang; Chuan-Jin Hou; Bin-bin Ye; Zefeng Wang; Jiming Bian (International Journal of Polymer Science)
Along with society’s progress, high-quality coatings are widely used. Although fluorinated polymers were successfully prepared by semicontinuous emulsion polymerization with surfactants, chlorotrifluoroethylene (CTFE), and acrylate monomers, the optimization collocation of surfactants still has room for improvement. The traditional emulsifiers are physically absorbed onto the surface of latex particles. The latex film generated by latex particles is unstable in water, which limits its application. Herein, a novel series of cationic quaternary ammonium polymerizable surfactant was selected because it can react with CTFE and acrylate monomers and can become a part of the polymers. We also studied the effects of emulsifier type on resultant emulsion properties. In addition, wonderful weatherability, water resistance, and antibacterial and antifouling of the multifunctional fluorinated films were observed, which would open up a bright future for coating industries.